Study on the style of translation of the culture-specific items of the Analects (Lunyu): analysis based on the parallel corpus compiling the versions of Pérez Arroyo and Suárez Girard (ALPHA. Journal of Arts, Literature and Philosophy, 2025)
The study of translation style is becoming increasingly significant in the field of Corpus-Based Translation Studies (CBTS). This research, grounded in a self-constructed parallel corpus, aims to analyze the stylistic profiles in the translation of culture-specific items in the Analects (Lunyu) by Pérez Arroyo (1999) and Suárez Girard (1997). This corpus, created through a combination of quantitative and qualitative methodologies, allows us to explore the stylistic characteristics at the lexical, syntactic, and discursive levels, and to identify the similarities and particularities among the translated versions, as well as the trends followed by the translators in addressing culture-specific items. Based on the results obtained, suggestions are provided for the translation of culture-specific items with the goal of enhancing future translations of this Confucian classic.
Keywords: Parallel corpus; culture-specific items; Analects; translation style